24. FAKTOR PENYEBAB PENUNDAAN KERJASAMA INDONESIATHAILAND DALAM MENANGANI PRAKTEK IUU FISHING DI INDONESIA - Norma Rani K. Z.; Hermini Susiatiningsih; Marten Hanura (Journal of International Relations Diponegoro, 2016)
Indonesia’s marine fisheries become targets of fishery crime because of the abundant fisheriesand marine resources. One of the fishery crimes that occurred is the practice of IllegalUnreported Unregulated (IUU) Fishing which mostly conducted by foreign vessels comingfrom neighboring countries such as Thailand. Indonesia seeks to cooperate with Thailand toaddress the practice of IUU fishing in Indonesian waters because of the losses incurres as aresult of IUU Fishing. One way to do is to establish bilateral agreements in the form of aMemorandum of Understanding on Fisheries Cooperation that took place in 2002-2006. Thecooperation has ended, and both countries are seeking to carry out a new partnership in 2013.But in fact the signing of the agreement has been delayed. The problem that arises is what thefactors that cause delay such cooperation are. This research aims to determine the factors thatled to postponement of the signing agreement. This research found that the Indonesia-Thailand cooperation has been delayed because there are some obstacles in the process ofsigning the agreement document such as factor the counter draft from each party and factor ofThailand political instability.